Bioenergetic Failure in Rat Oligodendrocyte Progenitor Cells Treated with Cerebrospinal Fluid Derived from Multiple Sclerosis Patients - Mathur, Deepali; Riffo-Campos, Angela L.; Castillo, Josefa; Haines, Jeffery D.; Vidaurre, Oscar G.; Zhang, Fan; Coret-Ferrer, Francisco; Casaccia, Patrizia; Casanova, Bonaventura; Lopez-Rodas, Gerardo (Frontiers in Cellular Neuroscience, 2017)
In relapsing-remitting multiple sclerosis (RRMS) subtype, the patient’s brain itself is capable of repairing the damage, remyelinating the axon and recovering the neurological function. Cerebrospinal fluid (CSF) is in close proximity with brain parenchyma and contains a host of proteins and other molecules, which influence the cellular physiology, that may balance damage and repair of neurons and glial cells. The purpose of this study was to determine the pathophysiological mechanisms underpinning myelin repair in distinct clinical forms of MS and neuromyelitis optica (NMO) patients by studying the effect of diseased CSF on glucose metabolism and ATP synthesis. A cellular model with primary cultures of oligodendrocyte progenitor cells (OPCs) from rat cerebrum was employed, and cells were treated with CSF from distinct clinical forms of MS, NMO patients and neurological controls. Prior to comprehending mechanisms underlying myelin repair, we determine the best stably expressed reference genes in our experimental condition to accurately normalize our target mRNA transcripts. The GeNorm and NormFinder algorithms showed that mitochondrial ribosomal protein (Mrpl19), hypoxanthine guanine phosphoribosyl transferase (Hprt), microglobulin β2 (B2m) and transferrin receptor (Tfrc) were identified as the best reference genes in OPCs treated with MS subjects and were used for normalizing gene transcripts. The main findings on microarray gene expression profiling analysis on CSF treated OPCs cells revealed a disturbed carbohydrate metabolism and ATP synthesis in MS and NMO derived CSF treated OPCs. In addition, using STRING program, we investigate whether gene-gene interaction affected the whole network in our experimental conditions. Our findings revealed downregulated expression of genes involved in carbohydrate metabolism, and that glucose metabolism impairment and reduced ATP availability for cellular damage repair clearly differentiate more benign forms from the most aggressive forms and worst prognosis in MS patients.